Medical Dispensary Organizer - Ghiye, Vikram; Avachat, Neha; Kulkarni, Pratik; Ujagare, Harshad; Navle, Vinod (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The project medical dispensary organizer system provide hospitals with medication management system that keeps inventory secure and organized .the chemist will be able to find the medicine tablets in an automated format and deliver medicine without any error, and when a doctor will prescribe to a certain tablet the chemist will be able to get it easily from the dedicated drawers. Automated medication distribution system provide computer-controlled storage, dispensing, and tracking of medications which is one of the potential mechanism to improve efficiency and patient safety.
Keywords: Python; Raspberry Pi